Insulin-Like Growth Factor Gene Polymorphisms Predict Clinical Course in Allogeneic Hematopoietic Stem Cell Transplantation - Ebbesen, Maria; Enevold, Christian; Juul, Anders; Heilmann, Carsten; Sengeløv, Henrik; Müller, Klaus (Frontiers in Immunology, 2020)
Allogeneic hematopoietic stem cell transplantation (HSCT) is challenged by significant toxicities that are propagated by systemic inflammation caused by cytotoxic damage. Insulin-like growth factor-1 (IGF-1) is key in repair of most tissues and is to a large extent genetically determined. We investigated eight single nucleotide polymorphisms (SNPs) in the genes encoding IGF-1 and its binding protein (IGFBP3) in 543 patients undergoing HSCT to access their impact on systemic inflammation and clinical outcomes. Overall, median serum levels of both IGF-1 and IGFBP3 were found reduced from the referral until two years post-HSCT compared with healthy sex- and age-matched individuals, but, for individuals homozygous of the known high-producer minor allele of rs1520220 (IGF1), rs978458 (IGF1) or rs2854744 (IGFBP3) serum levels remained normal during the whole period. In accordance, maximum C-reactive protein levels were lower for these genotypes of IGF1 (rs1520220: median 66 vs 102 mg/L, P = 0.005 and rs978458: 53 vs 104 mg/L, P < 0.001), translating into borderline significant superior survival (P = 0.060 for rs1520220) and reduced treatment-related mortality (P = 0.050 for rs978458). In conclusion, we found that three SNPs in the IGF-1 axis with known functional impact were associated with circulating IGF-1 or IGFBP-3 levels also in the setting of HSCT, and predictive of the severity of the toxic-inflammatory response during the treatment.